Estudios epidemiológicos en la interfase humano - animal - ecosistema. Factores relacionados al riesgo de infección de patógenos zoonóticos - Berra, Y. (2021)
One of the most important social phenomena in recent years is the close coexistence between animals -domestic companion or production, synanthropic and wild- and people, fulfilling various functions: social, cultural or economic and representing a relevant component of the welfare of community.\nThe fast and poorly planned urbanization and industrialization of agri-food production have favored the expression of risk factors for pathogen infection. At the same time, wild species, after altering their habitat, modify their range of action, being able to contact domestic species and humans. In order to analyze environmental variables and the risk of pathogen infection in the human-animal-ecosystem interface, we conducted studies in Buenos Aires city, in the Costanera Sur Ecological Reserve (RECS), in close relationship with precarious urbanized areas with high epidemiological risk -Barrio Rodrigo Bueno- considering as a model the study of Leptospira spp. Currently, studies are being carried out in areas where contact would be established in the human-animal-ecosystem interface of wild and domestic reservoirs with an impact on public and animal health due to their productive condition, considering as multi-host pathogenic models such as Cryptosporidium spp. and Giardia spp. in protected areas -Ciervo de los Pantanos National Park and Iberá National Park- and in the urban-rural area of the Exaltación de la Cruz district. These studies are fundamental since they contribute new aspects to the knowledge of the epidemiology of these diseases and innovative forms of monitoring using sentinel species to detect the risk of infection early and propose tools to incorporate into the health systems.